Tinjauan Etika Bisnis Islam terhadap Praktik Jual Beli Foto di Area Pintu Masuk Kebun Binatang Kota Bandung - Najmi Nurfauzi Ihsani; Panji Adam Agus Putra; Nanik Eprianti (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. The principles of Islamic business ethics emphasize the moral aspect or ethical values (ethics) that must be carried out by humans in carrying out economic activities or muamalah transactions. This is done to avoid losses experienced by one of the parties in the transaction as happened in the practice of buying and selling photos of tourists at the entrance area of the Bandung City Zoo, because the shooting activity was carried out without any request of the tourists themselves. Based on these problems, the purpose of the research is to analyze the practice of buying and selling photos between photographers and tourists in the Bandung City Zoo area and to find out an overview of the principles of Islamic business ethics towards buying and selling photos and photographer services in the Bandung City Zoo tourist area. The research method used is qualitative with an empirical juridical approach.This type a research uses field data, uses primary data sources in the form of interviews and secondary in the form of literature both in the form of books and journals with the data analysis technique used is descriptive analysis in the form descriptions of the practice of buying and selling photos in the Bandung City Zoo area in terms of Ethical Principles Islamic business. The results showed that the practice of buying and selling photos between photographers and tourists in the Bandung City Zoo area contained elements of coercion on the part of photographers to tourists, and the practice of buying and selling photos in the Bandung City Zoo Tourism Area was not in accordance with ethical values. Islamic business, especially from the aspect of the principle of Antaradhin. Abstrak. Prinsip-prinsip etika bisnis Islam menekankan kepada aspek moral atau nilai-nilai etiks (etika) yang harus dijalankan oleh manusia dalam melakukan aktivitas ekonomi atau transaksi muamalah. Hal ini dilakukan untuk menghindari kerugian yang dialami oleh salah satu pihak dalam bertransaksi seperti yang terjadi pada praktik jual beli foto wistawan di Kebun Binatang Kota Bandung, karena kegiatan pemotretan tersebut dilakukan tanpa adanya permintaan dari para wisatawan itu sendiri. Berdasarkan permasalahan tersebut, maka tujuan penelitian adalah untuk mengetahui praktik jual beli foto antara pihak fotografer dengan para wisatawan di area Kebun Binatang Kota Bandung dan untuk mengetahui tinjauan prinsip-prinsip etika bisnis Islam terhadap jual beli foto di area wisata Kebun Binatang Kota Bandung. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan yuridis empiris. Jenis penelitian menggunakan data lapangan, dengan menggunakan sumber data primer berupa wawancara dan sekunder berupa literatur baik dalam bentuk buku dan jurnal dengan teknik analisis data yang digunakan adalah deskriptif analisis berupa uraian praktik jual beli foto di area Kebun Binatang Kota Bandung ditinjau dari Prinsip-prinsip Etika Bisnis Islam. Hasil penelitian menunjukkan bahwa Praktik jual beli foto antara pihak fotografer dengan para wisatawan di area Kebun Binatang Kota Bandung mengandung unsur pemaksaan dari pihak fotografer kepada para wisatawan, dan praktik jual beli foto di Area Wisata Kebun Binatang Kota Bandung ini belum sesuai dengan Prinsip-prinsip Etika Bisnis Islam terutama dari aspek prinsip antaradhin.